Evaluasi hasil belajar siswa pada materi sistem pencernaan manusia melalui penerapan metode discovery learning di kelas VIII SMP Nurul Iman Palembang - RR. Mini Sariwulan; Abdul Hadi; Ra. Hoetary Tirta Amallia; Sugeng Setiyanto; Fairuzzabadi Amrullah; Muhammad Fauzi Romadhan (Jurnal Penelitian Pendidikan IPA, 2025)
The surge in diverse teaching methods necessitates systematic evaluation of their effectiveness. This study evaluated student learning outcomes in three domains (cognitive, psychomotor, and affective) following the discovery learning implementation on the human digestive system material in Grade VIII at Nurul Iman Middle School Palembang. Using a mixed-method approach, 36 students were assessed through: (1) a 20-item multiple-choice posttest including literacy questions, (2) poster creation evaluated by three observers using five aspect rubrics, and (3) self-evaluation questionnaires covering communication, discipline, teamwork, and character. Results revealed suboptimal cognitive achievement, with only 47% meeting the minimum completion criteria (≥70), though students demonstrated strong performance on literacy questions (61-83% correct). Psychomotor skills averaged 74 (sufficient category), showing varied creative abilities in applying digestive health knowledge. Affective outcomes averaged 80 (good category), indicating positive attitude development. The discovery learning method effectively fostered literacy skills and affective development but requires instructional refinement to optimize conceptual understanding and application in the cognitive domain.